2024
DOI: 10.31413/nat.v12i1.16922
|View full text |Cite
|
Sign up to set email alerts
|

Superabsorbent Polymers and Sanitary Sewage Change Water Availability During the Cowpea Emergence Phase

Edcássio Dias Araújo,
Miquéias Oliveira Assis,
Claudinei Martins Guimarães
et al.

Abstract: Superabsorbent polymers (SAP) enhance water retention and facilitate seed emergence, though studies predominantly use high-quality water, neglecting SAP performance with alternative sources like sanitary sewage. Addressing the imperative to reduce fresh water demand, especially in water-scarce regions, SAP and sanitary sewage emerge as potential agricultural alternatives, partially fulfilling crop water and nutritional needs. This study assessed the impact of SAP and synthetic sanitary sewage (SSS) on substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Another important factor regarding soil surface moisture is thermal regulation (Figure 2). This condition is favorable for the germination and proper establishment of cowpea during the hottest periods of the year because water present on the surface mitigates soil temperature [29]. Lower soil temperature reduces hypocotyl constriction and minimizes other physicochemical damage to seedlings, negatively affecting their establishment.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor regarding soil surface moisture is thermal regulation (Figure 2). This condition is favorable for the germination and proper establishment of cowpea during the hottest periods of the year because water present on the surface mitigates soil temperature [29]. Lower soil temperature reduces hypocotyl constriction and minimizes other physicochemical damage to seedlings, negatively affecting their establishment.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effect of temperature on the germination of P. peruviana seeds, constant temperatures of 10,15,20,25,30,35, and 40 • C were tested. Additionally, an alternating temperature of 20/30 • C was tested, following the same procedure described in the germination test in Section 2.1.…”
Section: Influence Of Temperature On Seed Germination and Vigormentioning
confidence: 99%
“…Germination decreased from −0.2 MPa to −0.6 MPa, reaching zero at −0.8 and −1.0 MPa. Oliveira et al [65] evaluated different osmotic potentials (0; −0.1; −0.2; −0.3; −0.4; −0.5; and −0.6 MPa) and temperatures (25,30,35, and 20/30 • C) on the germination of Simira gardneriana seeds. The authors observed that decreasing osmotic potential and increasing temperature led to a reduction in seed germination.…”
Section: Experiments Ii: Germination and Vigor Of Seeds Under Differe...mentioning
confidence: 99%
See 1 more Smart Citation